Complying with ethical principles in elderly and frail patients with advanced chronic kidney disease - Ana Mateus (Cadernos de Saúde)
Introduction: In 2016, in Europe (EU), 27.3 million people were aged > 80 (the so-called "elderly people"), and this value will likely increase up to 7 million more in ten years time. Portugal follows that world trend and has presently the fifth highest proportion of elderly people in the EU. According to the data records from the Portuguese Society of Nephrology, the cohort of dialysis patients aged > 80 years appears in the tables as an individualized group with a significant and increasing prevalence since 2015. Overtreatment of elderly patients ESRD has gained attention in professional journals and the lay mediafueled by disturbing outcome data. Therefore, it is imperative to review the application of dialysis treatment. Patients should be informed about the options of treatment, including the more conservative, non-dialytic ones and the implications of the different options for their lives. Aims: To analyze ethically the problems faced in renal replacement therapy resulting from the aging of the population in Portugal. Materials and methods: A critical review and analysis was conducted to discuss the dilemmas and challenges to deal with the above critical situation, namely the approach dialysis versus conservative treatments. Results: The basis for all processes involved are, namely: (i) the ethics´ principles that are the key support to guide the care providers through the treatment options; (ii) the estimation of prognosis and shared decision-making and (iii) the palliative care, which is an area where the awareness of clinicians needs to be urgently improved. Conclusions: It is crucial the presentation to the patients of the several options of treatment aiming to achieve a better balance between risks and benefits and the best possible response to the goals and expectations of the patients.